2007
DOI: 10.1111/j.1468-1331.2007.01723.x
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study on awareness of stroke in Turkey

Abstract: Stroke is the second most common cause of mortality and a major cause of long-term disability of adults in most countries. This study was performed to determine the level of knowledge and awareness regarding risk factors and warning signs of stroke in a selected sample. This cross-sectional study was carried out in Aydin between November and December 2005, utilizing a study sample of 920 people registered at urban health centers. The questionnaire, prepared by the investigators, was administered by 20 trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(83 citation statements)
references
References 19 publications
4
73
2
4
Order By: Relevance
“…However, less than one third of the general public can come up with more than two symptoms or risk factors and even fewer are considered to have an adequate knowledge of stroke or TIA. Similar results have been reported throughout the United States and across Europe and Asia (Kothari et al 1997, Pancioli et al 1998, Yoon et al 2001, Reeves et al 2002, Greenlund et al 2003, Parahoo et al 2003, Centers for Disease Control and Prevention 2004, Ferris et al 2005, Müller-Nordhorn et al 2006, Nedeltchev et al 2007, Evci et al 2007, Mikulík et al 2008. Women have been found to have a better overall symptom awareness and knowledge of risk factors than men (Ferris et al 2005).…”
Section: Knowledge Of Stroke Among the Publicsupporting
confidence: 75%
See 1 more Smart Citation
“…However, less than one third of the general public can come up with more than two symptoms or risk factors and even fewer are considered to have an adequate knowledge of stroke or TIA. Similar results have been reported throughout the United States and across Europe and Asia (Kothari et al 1997, Pancioli et al 1998, Yoon et al 2001, Reeves et al 2002, Greenlund et al 2003, Parahoo et al 2003, Centers for Disease Control and Prevention 2004, Ferris et al 2005, Müller-Nordhorn et al 2006, Nedeltchev et al 2007, Evci et al 2007, Mikulík et al 2008. Women have been found to have a better overall symptom awareness and knowledge of risk factors than men (Ferris et al 2005).…”
Section: Knowledge Of Stroke Among the Publicsupporting
confidence: 75%
“…General practitioners and other licensed health care workers were named by only 8-22% of the respondents. (Pancioli et al 1998, Parahoo et al 2003, Evci et al 2007) The sources of information have also varied considerably between different age groups and study settings. (Müller-Nordhorn et al 2006) The most commonly mentioned warning symptoms in these surveys have been…”
Section: Knowledge Of Stroke Among the Publicmentioning
confidence: 99%
“…15 Although previous studies have suggested that women, 6,8,10,12,13 and either young 10,13,16 or middle aged 12,14 patients have better knowledge and awareness of TIA and stroke the present study showed no sex or age-related differences in the responses obtained. Other reports have also highlighted that awareness of cerebrovascular disease is better in those with higher levels of education 6,8,[10][11][12]14,16,17 and higher income. 8,16,17 In this study 65% of respondents were socioeconomic class I and II and would be expected to be more knowledgeable suggesting that for the wider population appropriate responses to TIA are even less likely.…”
Section: Discussioncontrasting
confidence: 64%
“…Ancak ülkemizde hala gerek toplumda gerek sağlık profesyonelleri arasında tedavisi mümkün olmayan bir hastalık olarak algılanmaktadır (10,20).…”
Section: Introductionunclassified
“…İnme risk faktörlerinin farkındalığı inmeyi önlemede, inme alarm belirtileri farkındalığı ise acil tedaviye erişimde (4), akut inmede potansiyel tedavi seçeneklerinin arttırılmasında (revaskülarizasyon tedaviler; trombolitik ve mekanik trombektomi) ve inme sonrası daha iyi sonuçlar sağlamasında çok önemlidir (6,20,21,22,23,24,25).…”
Section: Introductionunclassified